Where Do Markets Come From? (translated by Gregory Yudin) - Harrison С. White (Journal of Economic Sociology, 2010)
Production markets have two sides: producers are a fully connected clique transacting with buyers as a separate but aggregated clique. Each producer is a distinctive firm with a distinctive product. Each side continually monitors reactions of the other through the medium of a joint social construction, the schedule of terms of trade. Each producer is guided in choice of volume by the tangible outcomes of other producers-not by speculation on hypothetical reactions of buyers to its actions. Each producer acts purely on self-interest based on observed actions of all others, summarized through a feedback process. The summary is the terms-of-trade schedule, which reduces to constant price only in limiting cases. The market emerges as a structure of roles with a differentiated niche for each firm. Explicit formulae-both for firms and for market aggregates are obtained by comparative-statics methods for one family of assumptions about cost structures and about buyers' evaluations of differentiated products. Not just any set of firms can sustain terms of trade with any set of buyers. There prove to be three main kinds of markets, and three sorts of market failure, within a parameter space that is specified in detail. One sort of market (PARADOX) has a Madison Avenue flavor, another is more conventional (GRIND), and a third (CROWDED) is a new form not included in any existing theory of markets. Current American industrial markets are drawn on for 20 illustrations, of which three are presented in some detail. Inequality in firms' market shares (measured by Gini coefficients) is discussed.